Really Existing Ghosts: A spectral reading of Conor McPherson's The Veil. (3rd April 2018) - Wolfe, Graham
Abstract : Conor McPherson's The Veil (2011) is a play about a haunted house set amidst a climate of economic hardship and socio-political unrest in rural Ireland of 1822. While many critics have located the appeal and force of McPherson's work in its capacity to inspire metaphysical wonder and curiosity for what exceeds the visible, this article argues that The Veil 's critical potentials arise in its conjuring of what I call, borrowing a term from Fabio Vighi, the 'really existing ghosts' of a British-imposed agrarian capitalism. And while this play travels far into the past, I suggest that its significance for twenty-first-century audiences emerges most forcefully through what Andrew Sofer calls 'spectral reading', an approach emphasizing the power of theatre's 'dark matter'. I argue for McPherson as an eminent playwright of dark matter, not only in the sense of metaphysical presences within, beneath or beyond his drama's naturalistic world. The socio-economic and socio-political climate of a play's dramatic world can itself operate powerfully as dark matter, its unseen and disavowed dimensions registering from the wings and threatening to intrude. Indeed, McPherson's theatre's most powerful and illuminating dark matter may consist in what is rendered invisible by characters' and audiences' attraction to the metaphysical.